Role of imaging in neonatal Chikungunya encephalitis acquired by vertical transmission - Sachdev, Namrita; Singh, Yashvant; Gupta, Shivani (Indian Journal of Child Health, 2018)
Background: Chikungunya is a viral infection which usually manifests as fever, rash, and arthralgia. Neurological complications are rare but are increasingly been seen in children and adults in endemic countries like India. Vertical transmission is seen in neonates with mothers who have been infected with the virus in the antenatal period. Objective: The objective of the study was to identify the essential role of imaging in the workup of these neonates, especially magnetic resonance imaging (MRI). Methods: A retrospective descriptive analysis of 10 neonates presenting with hypoactivity, maculopapular rash, and fever progressing to generalized seizures, and apnea suggestive of encephalitis was done. Chikungunya was confirmed by serum IgM CHICK enzyme-linked immune sorbent assay. Imaging evaluation included neurosonogram, computed tomography, and MRI with diffusion-weighted sequence with follow-up imaging at 1–3 months. Results: All the neonates had encephalopathy (100%) with or without seizures and perioral rashes. Cerebrospinal fluid showed mononuclear pleocytosis, raised protein or hypoglycorrhachia in 75% cases. Bacterial markers including cultures were negative. MRI showed features of viral encephalitis involving frontoparietal subcortical and deep white matter and corpus callosum with restricted diffusion. Neurocognitive outcomes in these neonates revealed neurodevelopmental delays for which follow-up MRI imaging was important, revealing reversal in diffusion changes, cystic encephalomalacia, and diffuse cerebral atrophy. Conclusion: In countries like India, experiencing annual outbreaks of Chikungunya infections radiologists must be familiar with the neuroimaging features and its possible sequelae.